KRIPTOSISTEM MENGGUNAKAN ALGORITMA GENETIKA PADA DATA CITRA - Pakereng, Magdalena Ariance Ineke (Jurnal Informatika, 2008)
Data and information security either those to be sent through the communication network or those to be kept in a device has brought into attention of the user of this information and data. Information and data security is being kept by making the data and information are not able to be read or known by unauthorized users. This can be done by using the cryptography technique. There are many cryptography techniques has been created to meet the above purpose. This research dealt with a new method in symmetric cryptosystem to encrypt digital image data using genetic algorithm. This method uses some components of genetic algorithm, the crossover operation and mutation operation, crossover rate and mutation rate, and fitness function. The process includes creating the encryption and decryption process using the crossover and mutation process. The crossover process illustrates the transposition technique, while the mutation process illustrates the substitution technique. This cryptosystem is applied to the 8-bit grayscale image using 2 (two) keys, random seed and number of generation. The result of the research shows that cryptosystem using the genetic algorithm is possible to be applied to the digital image. With 7000 or more as number of generation, plain image is possible to be encrypted into unrecognized cipher image, and by measuring the similarity of the image based on the pixel (pixel based similarity), the result of decipher image is similar with the plain image. The keys of the random seed affect the durability of the result of encryption process, while the sum of the generation affects the randomization of the cipher image and the running time (the time needed for the process).